2016
DOI: 10.1080/24701394.2016.1238902
|View full text |Cite
|
Sign up to set email alerts
|

The novel primers for mammal species identification-based mitochondrial cytochrome b sequence: implication for reserved wild animals in Thailand and endangered mammal species in Southeast Asia

Abstract: We presented the powerful techniques for species identification using the short amplicon of mitochondrial cytochrome b gene sequence. Two faecal samples and one single hair sample of the Asian tapir were tested using the new cytochrome b primers. The results showed a high sequence similarity with the mainland Asian tapir group. The comparative sequence analysis of the reserved wild mammals in Thailand and the other endangered mammal species from Southeast Asia comprehensibly verified the potential of our novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…DNA meta-barcoding has been successfully applied to the illegal orchid trade as well as in the identification of endangered species in complex samples. DNA mini-barcoding was utilized for the identification of highly processed animal skin and fur, wildlife skin samples, and samples of animal claws. The forensic analysis of cytochrome b (cyt b), a mtDNA gene, has become an essential tool for species identification in routine practice, and for this reason, a number of different primers were designed with species identification capabilities. Another study combined a morphometric approached with DNA analysis using cyt b and 16S rRNA genes to identify seized samples of tiger claws in India . Illegal trading of ivory is responsible for the decrease in elephant populations.…”
Section: Endangered Species and Wildlife Forensicsmentioning
confidence: 99%
“…DNA meta-barcoding has been successfully applied to the illegal orchid trade as well as in the identification of endangered species in complex samples. DNA mini-barcoding was utilized for the identification of highly processed animal skin and fur, wildlife skin samples, and samples of animal claws. The forensic analysis of cytochrome b (cyt b), a mtDNA gene, has become an essential tool for species identification in routine practice, and for this reason, a number of different primers were designed with species identification capabilities. Another study combined a morphometric approached with DNA analysis using cyt b and 16S rRNA genes to identify seized samples of tiger claws in India . Illegal trading of ivory is responsible for the decrease in elephant populations.…”
Section: Endangered Species and Wildlife Forensicsmentioning
confidence: 99%
“…The suitability of quantitative PCR for wildlife research was discussed by Powell et al (2019) in their study, in which they found that quantitative RT-PCR requires minimal sample input and can analyze low-quality samples and no post-PCR analysis ensures that samples are free of contaminants. Muangkram et al (2018) identified Asian tapir by sequencing a PCR-amplified 199bp fragment of the cytochrome gene using the NCBI BLAST tool. They describe the test as a reliable and sensitive molecular assay that can be used to analyze low-quality DNA material, which may be useful in investigating wildlife crime in endangered species.…”
Section: Dna-based Methods For Wildlife Conservationmentioning
confidence: 99%
“…Muangkram et al. (2018) identified Asian tapir by sequencing a PCR‐amplified 199‐bp fragment of the cytochrome gene using the NCBI BLAST tool. They describe the test as a reliable and sensitive molecular assay that can be used to analyze low‐quality DNA material, which may be useful in investigating wildlife crime in endangered species.…”
Section: Dna‐based Methods For Wildlife Conservationmentioning
confidence: 99%
“…This problem is solved by sequencing specific regions amplified with universal primers. The resulting sequences are compared with reference sequences using the BLAST search algorithm [12,13]. The SNP has become one of the most reliable markers for identifying animals from a biological sample since these mutations are numerous and widespread in the genomes of most animal species.…”
Section: Introductionmentioning
confidence: 99%